The taming of the queen [compact disc, unabridged] - Gregory, Philippa (Audioworks/Simon & Schuster Audio, 2015)
Kateryn Parr, 30 year old widow in a secret affair with a new lover, has no choice when a man old enough to be her father who has buried four wives, King Henry VIII, commands her to marry him. Kateryn has no doubt about the danger she faces: the previous queen lasted sixteen months, the one before barely half a year. But Henry adores his new bride and Kateryn's trust in him grows as she unites the royal family, creates a radical study circle at the heart of the court, and rules the kingdom.